Health and doping in elite-level cycling - Lentillon-Kaestner, V.; Hagger, Martin; Hardcastle, S. (Wiley-Blackwell, 2012)
The protection of the health of athletes is one of the three criteria taken into account when registering a substance in the World Anti-Doping Agency prohibited list. Nevertheless, in elite-level cycling, banned substance use is widespread. The present research adopted a psychological approach to examine how or whether perceived health risks influence elite-level cyclists' decisions to use banned substances. Sixteen semi-structured interviews were conducted with cyclists hoping to join a professional team (n=6), neo-professional cyclists (n=2), and former professional cyclists (n=8). Although an evolution was observed in the organization of doping and perceptions of doping over the last decade, the perceived health hazards did not influence, most of the time, decisions to use banned substances among the sample of cyclists. There was a systematization of exogenous substance use in the cycling environment and a trivialization of the side effects of the banned substances. Finally, younger cyclists were not concerned about the long-term health consequences of banned substances; they were more focused on the short-term performance-enhancing benefits. There is a need to implement more effective preventive programs to change athletes' attitudes toward doping and its health risks.